К фауне орибатид (Oribatidae) побережья Азовского моря - Ярошенко, Н.Н. (Вестник зоологии, 1972)
In 1969 the fauna of beetle mites was investigated on the Azov sea coast (the Donetsk region). 1650 mites are found belonging to 44 species, 36 genera and 27 families. The rare species Hermannia scabra (Koch) is found for the first time for the Ukraine and the new species Zygoribatula sp. n. is mentioned.